The role of asset markets for private consumption: evidence from paneleconometric models - Christian Dreger; Hans-Eggert Reimers (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We explore the long and short run relationship between private consumption, disposable income and housing and financial wealth approximated by price indices for a panel of industrialized countries. Consumption, income and wealth are cointegrated in their common, but not in their idiosyncratic components. This stresses the relevance of inter-national spillovers to explain aggregate consumption behaviour. The cointegrating vector is robust and in line with the life cycle permanent income hypothesis. The in-come elasticity does not differ from unity, and wealth elasticities are within a range of 2 to 5 percent. According to the error correction mechanism, consumption could not be interpreted as a weakly exogenous series.
Keywords: C23; E21; E32; G15; 330; Permanent income hypothesis; panel cointegration; wealth effects; Einkommenshypothese; Vermögenseffekt; Panel; Schätzung; Industriestaaten